2008
DOI: 10.1007/s00586-008-0678-x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous CT-guided biopsy of the spine: results of 430 biopsies

Abstract: Biopsies of lesions in the spine are often challenging procedures with significant risk of complications. CT-guided needle biopsies could lower these risks but uncertainties still exist about the diagnostic accuracy. Aim of this retrospective study was to evaluate the diagnostic accuracy of CT-guided needle biopsies for bone lesions of the spine. We retrieved the results of 430 core needle biopsies carried out over the past fifteen years at the authors' institute and examined the results obtained. Of the 430 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 14 publications
5
95
2
3
Order By: Relevance
“…In particular, CT guidance has been used for biopsy of a variety of sites within the body. [1][2][3][4]8,15,16,[20][21][22][23] This is largely attributed to an improved ability of the operator to identify the lesion and plan a trajectory for biopsy. CT-guided biopsy has been shown to be an effective tool in identifying pathology with relatively low risk and cost compared with open biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, CT guidance has been used for biopsy of a variety of sites within the body. [1][2][3][4]8,15,16,[20][21][22][23] This is largely attributed to an improved ability of the operator to identify the lesion and plan a trajectory for biopsy. CT-guided biopsy has been shown to be an effective tool in identifying pathology with relatively low risk and cost compared with open biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…CT-guided biopsy has been shown to be an effective tool in identifying pathology with relatively low risk and cost compared with open biopsy. 4,22,24 However, a frequently cited concern with CT scanning is the potential consequences of ionizing radiation, and there is much emphasis on limiting radiation to as low as reasonably achievable to obtain the necessary results whenever possible. 8,25 Previous studies have demonstrated the utility of a low-dose CT technique for a variety of interventional procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, trans-pedicular and trans-costovertebral approaches have been described [1,[3][4][5][6]9]. CT guidance has been described as safer than fluoroscopic guidance [10]; however, a recent meta-analysis has suggested no significant difference in complication rates (3.3-5.3%) [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the increased risks of infection, wound healing problems, hematoma formation, pathological fractures, and tumor contamination of healthy tissues, open biopsy should be performed only if a previously attempted percutaneous biopsy has been nondiagnostic. [1][2][3] In addition, excisional biopsy should be performed only for superficial, small (3 cm or less) lesions that can be excised with clear margins. 3 Moreover, in spinal and deep-seated pelvic lesions, an open biopsy can be a difficult procedure and has a significant risk of tumor spread and tissue contamination.…”
Section: How To Perform a Biopsymentioning
confidence: 99%